Anemia in Malaysian women with rheumatoid arthritis - Hussein, Heselyn; Othman, AZ; Shahar, Mohammad Arif (Asia Pacific League of Associations for Rheumatology and Wiley Publishing Asia Pty Ltd, 2014)
Aim: To determine the prevalence of anaemia among women with rheumatoid arthritis (RA) and determine its association between disease activity and disease modifying anti-rheumatic drugs (DMARDs)in a two-centre study between National University Malaysia Medical Centre and Putrajaya Hospital.